Finishing properties of Mahang Gajah (macaranga gigantea) by using different finishing systems and abrasive papers / Nur Azlina Abdul Basit - Abdul Basit, Nur Azlina (Faculty of Applied Sciences, 2016)
Finishing is used to provide protection and give aesthetic value to wood product. In this study, different finishing system (system A and system B) and abrasive paper were applied. Systems A consist of single layer of sealer meanwhile system B consist of double layer of sealer and for abrasive paper the silicon carbide and aluminum oxide been used in this study. From this study, it shows that there is significant different on finishing properties when using different finishing system meanwhile there is no significant different when using different abrasive paper on Mahang Gajah sample. System B had better finishing quality due to double layer of sealer that give excellent protection to Mahang Gajah wood surface. It can be concluded that system B give better protection on wood surface than system A and for abrasive paper it better to use silicon carbide because it is cheaper than aluminum oxide.